Rasch validation of the German translation of the Prosthetic Limb Users Survey of Mobility short forms in people with lower limb amputation - Bekrater-Bodmann, Robin; Kehl, Isabelle; Hafner, Brian J.; Ranker, Alexander; Giordano, Andrea; Franchignoni, Franco (Prosthetics and orthotics international, 2023)
Background: - Prostheses are a primary rehabilitative intervention for people after lower limb amputation. To appropriately measure the effectiveness of prosthetic interventions, valid and reliable measures of prosthetic mobility are required. The Prosthetic Limb Users Survey of Mobility (PLUS-M) is a promising instrument for measuring prosthesis users' mobility. However, German translations of the PLUS-M short forms have not yet been validated. - Objectives: - Rasch validation of the German translation of the PLUS-M short forms in people with lower limb amputation. - Study design: - This study is based on a cross-sectional survey of prosthesis-using lower limb amputees from a nation-wide cohort. - Methods: - PLUS-M data (the 7-item and the 12-item shortforms; PLUS-M-7 and PLUS-M-12, respectively) from 194 lower limb prosthesis users were subjected to Rasch analysis, an advanced statistical method for assessing if the measurement properties of a questionnaire comply with a wide spectrum of psychometric requirements. - Results: - Analysis showed appropriate rating scale functioning, good internal construct validity (item fit), unidimensionality, and good targeting of the PLUS-M-7 and PLUS-M-12 short forms. Moreover, the greater conditional measurement precision of PLUS-M-12 (regarding higher test information and lower standard error of mobility estimates) was quantified. - Conclusions: - Rasch analysis of the German translation of both PLUS-M short forms showed good psychometric qualities. In addition, our study showed that test scores from the PLUS-M-12 are more accurate. Therefore, the PLUS-M-12 is recommended for individual-level clinical applications (e.g., classification or change assessment).
Gesehen am 07.05.2024